Potensi Daun Tembelekan (Lantana Camara Linn.) Sebagai Anti-Agregasi Platelet dan Anti-Infl amasi Secara In Vivo - Ni Made Dwi Sandhiutami; Yesi Desmiaty; Nattika Sari Darmastuti; Fahri Muhammad (Fakultas Farmasi Universitas Pancasila, 2020)
Atherosclerosis is chronic inflammatory disease that can be prevented with anti-inflammatoryactivity agents and reduce thrombus formation in blood vessels. Tembelekan leaves (Lantana camaraLinn.) contain fl avonoids, saponins, and essential oils which potential to inhibit platelet aggregation andbe anti-inflammatory. This study aimed to test the in vivo anti-platelet aggregation and anti-inflammatoryactivity of tembelekan leaves. Platelet anti-aggregation test was carried out on mice by assessing thedecrease in plasma absorbance after addition of ADP. Mice were divided into normal group, positivecontrol group which was given clopidogrel and 3 test groups which were given Tembelekan leaf extractat a dose of 2.5, 5, 10 g/kgBW. In vivo anti-inflammatory test used the Winter method with intraplantar1% carrageenan as inducer. There was a signifi cant decrease in plasma absorbance after addition ofADP at doses of 2.5 and 5 g/kgBW of tembelekan leaves i.e 5.47% and 12.28% compared to thenormal group. Positive control and dose of 10 g/kgBW gave the same eff ect. In anti-inflammatorytest, the doses of 3.2 and 6.4 g/kgBW of tembelekan leaves gave percentage value of inhibition whichwas not signifi cantly diff erent with diclofenac sodium. Tembelekan leaves potentially as anti-plateletaggregation and anti-inflammatory properties.